Supervoid Origin of the Cold Spot in the Cosmic Microwave Background. Issue Volume 10:Issue S306(2014) (1st July 2015) - Kovács, András; Szapudi, István; Granett, Benjamin R.; Frei, Zsolt; Silk, Joseph; Burgett, Will; Cole, Shaun; Draper, Peter W.; Farrow, Daniel J.; Kaiser, Nicholas; Magnier, Eugene A.; Metcalfe, Nigel; et al.
Abstract: We use a WISE-2MASS-Pan-STARRS1 galaxy catalog to search for a supervoid in the direction of the Cosmic Microwave Background Cold Spot. We obtain photometric redshifts using our multicolor data set to create a tomographic map of the galaxy distribution. The radial density profile centred on the Cold Spot shows a large low density region, extending over 10's of degrees. Motivated by previous Cosmic Microwave Background results, we test for underdensities within two angular radii, 5°, and 15°. Our data, combined with an earlier measurement by Granett et al .2010, are consistent with a large R void =(192 ± 15)h −1 Mpc (2σ) supervoid with δ ≃ −0.13 ± 0.03 centered at z =0.22 ± 0.01. Such a supervoid, constituting a ∼3.5 σ fluctuation in the Λ CDM model, is a plausible cause for the Cold Spot.